ANALISIS MODEL PEMBELAJARAN JARAK JAUH BERBASIS WA PADA MASA PANDEMI COVID-19 DI KELAS V SEKOLAH DASAR NEGERI 28 PONTIANAK UTARA - Nurul Sapitri; Suparjan Suparjan; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the implementation of the WA-based distance learning model during the Covid-19 pandemic in class V of the 28 North Pontianak State Elementary School. This research is included in the descriptive type of qualitative research. The data collection techniques in this study used interviews, observations and questionnaires with thematic teachers and 29 VC class students as informants. The qualitative data analysis technique used is the Miles and Hubermen interactive model. To test the credibility of the data on the research results using triangulation techniques. The results of the analysis show that the implementation of the distance learning model has been carried out quite well, the teacher has prepared planning and carried out learning quite well by using methods that are adapted to the needs of students during the Covid-19 pandemic. However, distance learning also has obstacles in its implementation, the limited availability of students' mobile phones and internet networks, and the difficulty of teachers in monitoring students' understanding of the material presented. However, the perception of VC class students mostly showed a positive response to the implementation of the distance learning model during the Covid-19 pandemic.Keywords: analysis, WA-based distance learning model,Covid-19 pandemic